Analytic hierarchy process evaluation model for the introduction of talents among university teachers - Yanchen, Xu (Frontiers in Education, 2026)
In this paper, a quantitative evaluation model based on the Analytic Hierarchy Process (AHP) is constructed to addresses the issues of ambiguous evaluation criteria and strong subjectivity in the current talent recruitment process in universities. Firstly, a visible ability evaluation system consisting of 2 first-level indicators and 9 second-level indicators was established. Secondly, the AHP method was used to calculate the weights of each indicator, among which academic papers (0.303) had the highest weight. Finally, an empirical analysis was conducted by using the talents recruited from 2019 to 2024 as samples, verifying the validity of the model. This provides a scientific and systematic evaluation method for talent recruitment in universities and helps improve the quality of talent recruitment.